Antiplatelet therapy and the risk of hepatocellular carcinoma in chronic hepatitis B patients on antiviral treatment. Issue 5 (29th September 2017) - Lee, Minjong; Chung, Goh Eun; Lee, Jeong‐Hoon; Oh, Sohee; Nam, Joon Yeul; Chang, Young; Cho, Hyeki; Ahn, Hongkeun; Cho, Young Youn; Yoo, Jeong‐ju; Cho, Yuri; Lee, Dong Hyeon; et al.
Abstract : Antiplatelet therapy has shown protective effects against hepatocellular carcinoma (HCC) in preclinical studies. However, it is unclear whether antiplatelet therapy lowers the risk of HCC in patients with chronic hepatitis B. A retrospective analysis was conducted of data from 1, 674 chronic hepatitis B patients, enrolled between January 2002 and May 2015, whose serum hepatitis B virus DNA levels were suppressed by antivirals to <2, 000 IU/mL. The primary and secondary outcomes were development of HCC and bleeding events, respectively. Risk was compared between patients with antiplatelet treatment (aspirin, clopidogrel, or both; antiplatelet group) and patients who were not treated (non‐antiplatelet group) using a time‐varying Cox proportional hazards model for total population and propensity score–matching analysis. The antiplatelet group included 558 patients, and the non‐antiplatelet group had 1, 116 patients. During the study period, 63 patients (3.8%) developed HCC. In time‐varying Cox proportional analyses, the antiplatelet group showed a significantly lower risk of HCC (hazard ratio [HR], 0.44; 95% confidence interval [CI], 0.23–0.85; P = 0.01), regardless of antiplatelet agent. In propensity score–matched pairs, antiplatelet therapy significantly reduced the risk of HCC (HR, 0.34; 95% CI, 0.15‐0.77; P = 0.01). However, the overall risk of bleeding was higher in the antiplatelet group (HR, 3.28; 95% CI, 1.98‐5.42; P < 0.001), particularly for clopidogrel with or without aspirin. Treatment with aspirin alone was not associated with a higher bleeding risk (HR, 1.11; 95% CI, 0.48‐2.54; P = 0.81). Conclusion : Antiplatelet therapy reduces the risk of HCC in chronic hepatitis B patients whose hepatitis B virus is effectively suppressed. However, antiplatelet therapy containing clopidogrel may increase the risk of bleeding. (Hepatology 2017;66:1556–1569)